The preparation and antibacterial effect of egg yolk immunoglobulin (IgY) against the outer membrane proteins of Vibrio parahaemolyticus. (4th December 2018) - Hu, Bochao; Yang, Xiaodong; Guo, Erpeng; Zhou, Peizhan; Xu, Ding; Qi, Zhenqiang; Deng, Li
Abstract: BACKGROUND: Vibrio parahaemolyticus causes not only various diseases in aquaculture animals but also seafood‐borne illness in humans. Outer membrane proteins (OMPs) are species‐specific proteins found in bilayer membranes of gram‐negative bacteria. Egg yolk immunoglobulin (IgY) has been reported to serve as oral administration of antibodies against bacteria and virus. RESULTS: The present research extracted and identified OMPs from V. parahaemolyticus, and then the extracted OMPs were used to immunize hens to obtain specific IgY. The efficacy of IgY against V. parahaemolyticus were investigated in vitro and in vivo . The specific IgY effectively inhibited the growth of V. parahaemolyticus in liquid medium rather than Escherichia coli and Staphylococcus aureus . Specific IgY antibodies were incorporated into extruded food pellets and fed to bacteria‐challenged white pacific shrimp to observe the anti‐bacterial effect in vivo . The bacterial loads in muscles of V. parahaemolyticus infected shrimp fed with specific IgY‐included diets were significantly fewer than those fed with non‐specific IgY‐included diets. The superoxide dismutase activities in muscles of infected shrimp fed with specific IgY‐included diets were significantly higher than the control group. CONCLUSION: The results suggested that the specific IgY effectively inhibited the growth of V. parahaemolyticus and introduced passive immunity to shrimp. © 2018 Society of Chemical Industry